Ekonomi Kreatif sebagai Upaya Pemberdayaan Masyarakat di Bidang Ekonomi - Nadhia Putri Firnanda; Solfema Solfema; Lili Dasa Putri (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
Community empowerment is a conscious and planned effort carried out by the community to make those who cannot or are incapable become capable by utilizing the potential that exists in their environment. After identifying the problem that low community income is caused by people not having sufficient knowledge and skills to help improve the economy or increase their family income through the creative economy, the aim of this article is to explain efforts to empower the community in the economic sector through the creative economy.